The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15446/acag.v67n2.60866
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest quality of strawberry (Fragaria × ananassa (Duchesne ex Weston) Duchesne ex Rozier) genotypes according to vernalization

Abstract: Strawberry production in Paraguay is carried out by small producers, using minimal technology and obtaining low productivity, with the need to expand strawberry genotypes and production techniques. The aim of this study was to evaluate fruit quality of strawberry genotypes according to vernalization. A randomized block design with factorial arrangement 14x2 was performed; factors were genotypes and chilling using 15 plants per treatment and three replicates. Plants were kept in cold room at 5°C, with 8 hours o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…It can be observed that low temperatures are more suitable for having more TA, as found in all cultivars planted on 5 April compared to those planted on 20 April. The same results were reported by Santacruz Oviedo et al (2018), who demonstrated that vernalisation of strawberry plants had no effect on berry shape or SSC, although it caused an increase in TA. Strawberry plants planted on 5 April had a higher chlorophyll content, which is represented as an indicator of leaf photosynthesis (Okatan et al, 2022).…”
Section: Ssc Ph Ec Ta Ssc/ta and Chlorophyllsupporting
confidence: 88%
“…It can be observed that low temperatures are more suitable for having more TA, as found in all cultivars planted on 5 April compared to those planted on 20 April. The same results were reported by Santacruz Oviedo et al (2018), who demonstrated that vernalisation of strawberry plants had no effect on berry shape or SSC, although it caused an increase in TA. Strawberry plants planted on 5 April had a higher chlorophyll content, which is represented as an indicator of leaf photosynthesis (Okatan et al, 2022).…”
Section: Ssc Ph Ec Ta Ssc/ta and Chlorophyllsupporting
confidence: 88%
“…Palatability is determined by the ratio of total soluble solids (reference index used to quantify the number of soluble sugars) (Scalisi & O'Connell 2021) and titratable acidity (TA). High values of this ratio, respond to higher percentages of total soluble solids (TSS) and lower TA, behaviour reported in species such as Fragaria × ananassa (Santacruz-Oviedo et al 2018) and Vaccinium spp. (Medeiros et al 2017) for which TSS/TA ratio values of up to 54.83 and 20.57, respectively, were reported.…”
Section: Discussionmentioning
confidence: 88%
“…It is worth mentioning that Jpd (J. tlaxcala), considered semi-domesticated and closely linked to the traditionally managed agro-ecosystem, is more appreciated for its more palatable fruits, because they are sweeter and almost never acidic, compared to the purple or black fruits of J. procumbens (Williams 1985). This characteristic is mainly due to the palatability of the fruit, where high palatability values are important in determining consumer acceptance of a product (Santacruz-Oviedo et al 2018). Palatability is determined by the ratio of total soluble solids (reference index used to quantify the number of soluble sugars) (Scalisi & O'Connell 2021) and titratable acidity (TA).…”
Section: Discussionmentioning
confidence: 99%